The Habit of Reading Asmaul Husna to Improve Students' Character - Riska Anita Tama; Mohammad Zakki Azani (JIE (Journal of Islamic Education), 2024)
This study aims to describe the implementation of Asmaul Husna habituation in PAI learning in improving religious character at SMKN 1 Boyolali. This study used qualitative research methods. This research was conducted by observation and interviews with Islamic Education teachers and some students as well as documentation. Data reduction, presentation, and conclusion are the data analysis techniques used. Testing the validity of the data is a triangulation of sources, methods and time. The results of this study state that applying the habit of reading Asmaul Husna makes students aware of the sins they commit. This is because when the beautiful name of Allah Swt is mentioned or mentioned, it will tremble the heart, so students who have faith will be aware of their sins and be moved to continue to improve themselves and their character. Therefore, this motivates students to improve their attitudes and behaviour, which is a process of enhancing religious character. In addition, it can also raise awareness of the existence of Allah Swt so that this feeling will improve the religious character of students.